Acceptability and suitability of Tuta absoluta eggs from irradiated parents to parasitism by Trichogramma nerudai and Trichogramma pretiosum (Hymenoptera: Trichogrammatidae). (22nd March 2016) - Cagnotti, Cynthia L.; Hernández, Carmen M.; Andormo, Andrea V.; Viscarret, Mariana; Riquelme, María; Botto, Eduardo N.; López, Silvia N.
Abstract: Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is one of the most devastating pests of tomato crops. We studied the acceptability and suitability of eggs laid by irradiated T. absoluta pairs to parasitism by the parasitoids Trichogramma nerudai and Trichogramma pretiosum . Trichogramma absoluta pupae were irradiated with X‐radiation (20834 R) and the emerged adults were separated into couples according to the crosses: ♂U × ♀U, ♂I × ♀U, ♂U × ♀I (where 'U' is untreated and 'I' is irradiated). In a no‐choice experiment, 40 eggs from each cross were exposed to a female parasitoid for 24 h. All T. absoluta eggs were accepted for oviposition by T. nerudai and were suitable for its development. However, eggs from irradiated females were significantly less parasitized than those from untreated females. Trichogramma pretiosum showed low parasitism on eggs from all crosses. In a choice experiment, both T. nerudai and T. pretiosum showed no differences in the parasitism of eggs from irradiated ( n = 40) and non‐irradiated female moths ( n = 40). These results indicate that eggs laid by irradiated parents were acceptable for oviposition and suitable for the development of these parasitoids, and also support the idea that the inherited sterility technique could be used in an integrated approach with egg parasitoids to control T. absoluta.